2014
DOI: 10.1246/cl.140684
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5,6,11-Trideoxytetrodotoxin

Abstract: 5,6,11-Trideoxytetrodotoxin, a naturally occurring analog of tetrodotoxin, was synthesized from a synthetic intermediate of 5-deoxytetrodotoxin by continuous radical deoxygenation of two hydroxy groups at the C-6 and C-11 positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
18
0
3
Order By: Relevance
“…TTX (1) (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006), CHTX (2) (Adachi et al, 2014a), 8-deoxyTTX (3) (Satake et al, 2014), 4,9-anhydroTTX (4) (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006), 4,9-anhydroCHTX (5), 4,9-anhydro-8-deoxyTTX (6), 5-deoxyTTX (7) (Satake et al, 2014), 5,11-dideoxyTTX (8) (Nishikawa et al, 1999;Asai et al, 2001;Yotsu-Yamashita et al, 2013), 5,6,11-trideoxyTTX (9) (Adachi et al, 2014b), 4,9-anhydro-5-deoxyTTX (10) (Satake et al, 2014), 4,9-anhydro-5,11-dideoxyTTX (11) (Nishikawa et al, 1999;Asai et al, 2001;Yotsu-Yamashita et al, 2013) and 4,9-anhydro-5,6,11-trideoxyTTX (12) (Adachi et al, 2014b) were synthesized as reported in the literature (Figure 1 KOD-Plus, T4 ligase and the In-Fusion HD Cloning kit were purchased from Takara Bio, Inc. (Kusatsu, Shiga, Japan). PCR primers were purchased from Fasmac Co., Ltd. (Atsugi, Kanagawa, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…TTX (1) (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006), CHTX (2) (Adachi et al, 2014a), 8-deoxyTTX (3) (Satake et al, 2014), 4,9-anhydroTTX (4) (Ohyabu et al, 2003;Nishikawa et al, 2004;Urabe et al, 2006), 4,9-anhydroCHTX (5), 4,9-anhydro-8-deoxyTTX (6), 5-deoxyTTX (7) (Satake et al, 2014), 5,11-dideoxyTTX (8) (Nishikawa et al, 1999;Asai et al, 2001;Yotsu-Yamashita et al, 2013), 5,6,11-trideoxyTTX (9) (Adachi et al, 2014b), 4,9-anhydro-5-deoxyTTX (10) (Satake et al, 2014), 4,9-anhydro-5,11-dideoxyTTX (11) (Nishikawa et al, 1999;Asai et al, 2001;Yotsu-Yamashita et al, 2013) and 4,9-anhydro-5,6,11-trideoxyTTX (12) (Adachi et al, 2014b) were synthesized as reported in the literature (Figure 1 KOD-Plus, T4 ligase and the In-Fusion HD Cloning kit were purchased from Takara Bio, Inc. (Kusatsu, Shiga, Japan). PCR primers were purchased from Fasmac Co., Ltd. (Atsugi, Kanagawa, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The enantioselective syntheses of 5,11‐dideoxyTTX, 11‐deoxyTTX, and 8,11‐dideoxyTTX were achieved before the synthesis of (−)‐TTX and feature the synthesis of the natural product based on a Diels–Alder strategy from levoglucosenone. The same approach also gave rise to the syntheses of 5,6,11‐trideoxyTTX, 5‐ and 8‐deoxyTTX later. The other synthesis of 5,6,11‐trideoxyTTX was reported by Ohfune and Shinada .…”
Section: Synthesis Of Ttxmentioning
confidence: 93%
“…Recently, the alkaloids 22 and 400 (as well as 23 ) have been synthesized by Nishikawa and Isobe from acetal 410 , an O ‐ethyl analogue of compound 365 (cf. Section 6.1.2), by consecutive radical deoxygenation of two hydroxyl groups at the carbons C‐6 and C‐11, Scheme .…”
Section: Synthesis Of Ttx Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…Die enantioselektiven Synthesen von 5,11‐DideoxyTTX, 11‐DeoxyTTX und 8,11‐DideoxyTTX gelangen vor der Synthese von (−)‐TTX und zeichnen sich durch die Synthese des Naturstoffs basierend auf einer Strategie über eine Diels‐Alder‐Reaktion von Levoglucosenon aus. Aus derselben Vorgehensweise gingen später auch die Synthesen von 5,6,11‐TrideoxyTTX, 5‐ und 8‐DeoxyTTX hervor. Eine weitere Synthese von 5,6,11‐TrideoxyTTX wurde von Ohfune und Shinada berichtet .…”
Section: Synthese Von Ttxunclassified